2008
DOI: 10.1088/1126-6708/2008/04/037
|View full text |Cite
|
Sign up to set email alerts
|

Mesons in marginally deformed AdS/CFT

Abstract: We study the embedding of spacetime filling D7-branes in β-deformed backgrounds which, according to the AdS/CFT dictionary, corresponds to flavoring β-deformed N = 4 super Yang-Mills. We consider supersymmetric and more general non-supersymmetric three parameter deformations. The equations of motion for quadratic fluctuations of a probe D7-brane wrapped on a deformed three-sphere exhibit a non-trivial coupling between scalar and vector modes induced by the deformation. Nevertheless, we manage to solve them ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 76 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…Similar effects (a change in the mass spectrum proportional to the deformation parameter) happen when studying mesons in field theories dual to TsT deformations [61,62] of a given background.…”
Section: ( N+9)( N+10)mentioning
confidence: 74%
“…Similar effects (a change in the mass spectrum proportional to the deformation parameter) happen when studying mesons in field theories dual to TsT deformations [61,62] of a given background.…”
Section: ( N+9)( N+10)mentioning
confidence: 74%
“…For the N = 2 * case, it was shown in [120] that the meson mass obtained from the D7 probe brane fluctuations receives a contribution from the adjoint scalar quark mass, such that there is a mass gap. Recently [122], the embedding of a D7 brane probe into the Lunin-Maldacena background [123] was considered, which is dual to a N = 1 supersymmetric marginal deformation of N = 4 super Yang-Mills theory. Here, a Zeeman-like spitting of the mass spectrum is observed.…”
Section: B Fields In the Background: Polchinski-strassler Dualmentioning
confidence: 99%
“…In [150] probe D7 branes were numerically embedded in the nonsupersymmetric Yang-Mills * deformation [71] of the N = 4 theory providing evidence for chiral symmetry breaking. Quarks have also been added to the beta-deformed N = 4 theory in [122] -chiral symmetry breaking is again observed. It appears to be generically true that breaking supersymmetry in gravity duals leads to chiral symmetry breaking.…”
Section: More Chiral Symmetry Breakingmentioning
confidence: 99%
“…Thus we find the linear potential relation 8) in which the effective tension τ ef f is a decreasing function of the dipole field strength. At long separation limit L → ∞, i.e.…”
Section: Quark and Anti-quark Potentialmentioning
confidence: 72%
“…The first study of chiral dynamics in [3] used the Constable-Myers geometry [5]. Several scenarios in which supersymmetry breaking leads to chiral symmetry breaking have also been found -for example a set-up of D4 wrapped a circle which describes gauge theory in IR [6], placing the gauge theory on an anti-de-Sitter space [7], on the Lunin-Maldacena background [8,9], or introducing a background magnetic field [10,11]. The meson spectroscopy therein had also been studied (A recent review could be found in [12]) .…”
Section: Introductionmentioning
confidence: 99%